2018
DOI: 10.1074/jbc.ra117.001080
|View full text |Cite
|
Sign up to set email alerts
|

An efficient platform for generating somatic point mutations with germline transmission in the zebrafish by CRISPR/Cas9-mediated gene editing

Abstract: Homology-directed recombination (HDR)-mediated genome editing is a powerful approach for both basic functional study and disease modeling. Although some studies have reported HDR-mediated precise editing in nonrodent models, the efficiency of establishing pure mutant animal lines that carry specific amino acid substitutions remains low. Furthermore, because the efficiency of nonhomologous end joining (NHEJ)-induced insertion and deletion (indel) mutations is normally much higher than that of HDR-induced point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 66 publications
1
71
0
Order By: Relevance
“…Levels of mosaicism in gene targeting using HMEJ in zebrafish vary greatly in the reported literature (Hisano et al 2015) (Wierson et al 2018). Consistent with the observation that SAMR in noto:RFP-DR 48 is mosaic, it was recently reported that translation of Cas9 mRNA and subsequent gene editing after one-cell stage injection is not complete until the 16 or 32 cell stage while RNP injections result in appreciable nuclease activity by the 2-4 cell stage (Zhang, Zhang, and Ge 2018). Thus, noto:RFP-DR 48 is an assay system where injection conditions can be optimized to enhance somatic gene targeting and decrease mosaicism in cell types that arise from the mesoderm.…”
Section: Discussionsupporting
confidence: 77%
“…Levels of mosaicism in gene targeting using HMEJ in zebrafish vary greatly in the reported literature (Hisano et al 2015) (Wierson et al 2018). Consistent with the observation that SAMR in noto:RFP-DR 48 is mosaic, it was recently reported that translation of Cas9 mRNA and subsequent gene editing after one-cell stage injection is not complete until the 16 or 32 cell stage while RNP injections result in appreciable nuclease activity by the 2-4 cell stage (Zhang, Zhang, and Ge 2018). Thus, noto:RFP-DR 48 is an assay system where injection conditions can be optimized to enhance somatic gene targeting and decrease mosaicism in cell types that arise from the mesoderm.…”
Section: Discussionsupporting
confidence: 77%
“…Another strategy is to use small molecules to improve HDR efficiency by suppressing the activity of the NHEJ pathway or boosting the activity of the HDR pathway. Recently, the Ge group reported that using Cas9 protein instead of mRNA, suppression of NHEJ with SCR7 and stimulation of HDR pathways with RS-1 in combination could increase the efficiency of germline transmission of point mutations up to 25% in zebrafish [24]. However, these chemical treatments influence the endogenous DNA repair processes and may be toxic during embryonic development as a result [25].…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect hindering a direct comparison with several previous studies is the different methods used to evaluate the HDR efficiency, such as PCR-or restriction-assays, sequencing of a limited number of clones, genotyping based on high-resolution melting analysis, fluorescence etc. [37][38][39][40]42,44,46 . Only three studies in zebrafish have used NGS, showing lower perfect repair rates of 1-4% 41 , 1.7-3.5% 45 and <1% 43 .…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of very low efficiency KI of a gene encoding red fluorescent protein in rohu carp 34 , such advanced and fine-tuned genome editing has not been developed for farmed fish, and it may be useful to learn from protocols already established in model fish species. While only a few studies have reported HDR in medaka 35,36 , several KI-strategies have been reported in zebrafish using either donor plasmids [37][38][39] or single-stranded oligodeoxynucleotides (ssODNs) [40][41][42][43][44][45] , or both 46 . Knowledge from other fish studies are somewhat inconclusive when it comes to deciding the strategy for applying HDR in salmon, as there is a lack of consensus regarding the impact of different repair templates, homology arm length and strand complementarity in the above-mentioned studies.…”
mentioning
confidence: 99%